Melena as a first sign of metastatic hepatic angiosarcoma: A case report - Sokic-Milutinovic, Aleksandra; Toncev, Ljubisa; Glisic, Tijana; Matovic, Vera; Micev, Marjan; Djuranovic, Srdjan; Krstic, Miodrag (Vojnosanitetski pregled, 2021)
Abstract Introduction. Angiosarcomas are malignant tumors of vascular endothelium that may arise from different locations. Although primary hepatic angiosarcoma accounts for only 1.8% of primary liver tumors, it is the most common malignant mesenchymal tumor of the liver. We report a case of primary hepatic angiosarcoma with melena as an unusual initial manifestation of this extremely rare tumor. Case report. Forty-four-years old patient with melena was referred to our Clinic because melena was not resolved after repeated argon plasma coagulation of bleeding lesions during esophagogastroduodenoscopy in the regional hospital. Abdominal ultrasound and multislice computed tomography (MSCT) revealed enlarged liver, with focal lesion 6 cm in diameter localized in the left lobe with multiple satellite lesions in both liver lobes, enlarged spleen and extremely dilated and long umbilical vein. Double-balloon enteroscopy and video capsule endoscopy detected the multiple bleeding vascular lesions in the small bowel. Histopathological examination and immunohistochemistry of the small bowel lesions revealed malignant mesenchymal proliferation with vascular/endothelium differentiation of neoplastic cells. The patient was diagnosed with metastatic angiosarcoma probably of hepatic origin with metastasis in the small bowel, that caused melena, and in the lumbar spine, causing back pain. Conclusion. Rare causes of melena include bleeding from primary or metastatic hemangiosarcoma localized in the gastrointestinal tract, especially small bowel.